2019
DOI: 10.1002/jcp.29170
|View full text |Cite
|
Sign up to set email alerts
|

Long intergenic noncoding RNA 00641 inhibits breast cancer cell proliferation, migration, and invasion by sponging miR‐194‐5p

Abstract: Long noncoding RNAs have an essential role in the tumorigenesis of breast cancer (BC). Nonetheless, the consequences of long intergenic noncoding RNA 00641 (LINC00641) in BC remain unidentified. This study shows that LINC00641 expression level was decreased in BC tissues. LINC00641 expression level was negatively related to tumor size, lymphnode metastasis, as well as clinical stage. LINC00641 overexpression inhibited cell proliferation, migration, and invasion but stimulated apoptosis in BC cells. LINC00641 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…SNHG18 promotes resistance of glioma to radiotherapy by repressing semaphorin 5A [45]. LINC00641 expression level was found to be decreased in breast cancer tissue, which was negatively related to tumor size, lymph node metastasis, and clinical stage [46]. SNAI3-AS1 could bond up-frameshift protein 1 (UPF1), regulate Smad7 expression, and activate TGF-β/Smad pathway, to induce EMT in hepatocellular carcinoma [47], and it also acts an important factor in the ceRNA network in Adipose Tissue From Type 2…”
Section: Discussionmentioning
confidence: 93%
“…SNHG18 promotes resistance of glioma to radiotherapy by repressing semaphorin 5A [45]. LINC00641 expression level was found to be decreased in breast cancer tissue, which was negatively related to tumor size, lymph node metastasis, and clinical stage [46]. SNAI3-AS1 could bond up-frameshift protein 1 (UPF1), regulate Smad7 expression, and activate TGF-β/Smad pathway, to induce EMT in hepatocellular carcinoma [47], and it also acts an important factor in the ceRNA network in Adipose Tissue From Type 2…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that LINC00461 that serves as competitive endogenous RNA of microRNA-942 could affect the survival of patients with renal cell carcinoma (23). As for breast cancer, the expression level of LINC00641 was negatively correlated with the size of tumor, lymph node metastasis, and clinical stage, which could restrain the proliferation and migration of breast cancer cells (24). lncRNA DGCR9 was up-regulated in gastric cancer tissues, which played the role of promoting cell proliferation, migration and glucose metabolism, and of great importance for the progress of gastric cancer (25).…”
Section: Discussionmentioning
confidence: 98%
“…As far as BC is concerned, the inhibition of miR-194-5p in MCF7 cells was shown to correlate with decreased proliferation, migration and tumor growth [ 69 ], while in HER2 overexpressing BCCs, miR-194 knockdown promoted cancer cell migration and invasion [ 70 ]. Mao et al reported that the overexpression of miR-194-5p in both MCF7 and MDA-MB-231 cells promoted BCC proliferation, migration and invasion, while repressing cell death [ 71 ]. In accordance, in our in vitro system, 4T1 cells alone and in mixed culture, released and expressed miR-194-5p, especially in ‘metastasis-like’ clusters, being particularly evident in more marginal, possibly more invasive/migratory cells.…”
Section: Discussionmentioning
confidence: 99%